Design of Helical Coil-Gun Based on Self-Induction Coefficient and Projectile Size Optimization - Ege, Yavuz; Citak, Hakan; Bicakci, Sabri; Gunes, Huseyin; Coramik, Mustafa (Electrical, Control and Communication Engineering, 2026)
Electromagnetic Launcher (EML) systems are classified into two main categories based on their fundamental operating principles: rail guns and coil guns. Rail guns accelerate a conductive projectile using magnetic force by passing a high current between two parallel rails, but they suffer from wear and heat accumulation due to mechanical contact. Coil launchers use electromagnets to accelerate ferromagnetic or conductive projectiles without contact, thus minimising energy losses and wear. Rail guns are preferred in military applications requiring high velocity and kinetic energy, whereas coil guns are more prominent in controlled acceleration applications such as space launch systems and laboratory experiments. Since the velocity of the generated electromagnetic field in coil launchers has no theoretical limit, the accelerated projectile also does not have a predefined velocity limit. However, the use of randomly sized coils and an increased number of sequential coils in coil guns disrupts the linearity of the projectile velocity increase. To address this issue, this study develops a “New Helical Coil Gun”, consisting of four-stage helical coils designed to achieve linear velocity increase. First, the self-inductance coefficient of a coil was simulated based on the time-dependent variations of the current passing through it, and the inductance value that could provide a maximum instantaneous current of 25A (without direction change) under laboratory conditions was determined. Then, the design of the helical coil with a rectangular cross-section to provide this coefficient value was implemented. This design was then transferred to the ANSYS Maxwell magnetic analysis software, where an optimisation process was conducted to determine the ideal projectile size that would maximise the magnetic force exerted on a ferromagnetic projectile when a 25 A current was applied to the coil. Following this stage, a “Helical Coil Gun”, composed of four-stage helical coils, was designed and manufactured based on the determined projectile and coil dimensions. Optical sensors were placed at the initial positions of the coils to measure the projectile’s velocity. An FPGA-based project was developed for data acquisition, processing, and triggering control. This project, designed using the LabVIEW FPGA module, was carried out on the NI myRIO-1950 board containing Xilinx FPGA. After each launch, the collected data was stored on a flash drive connected to myRIO and monitored in real time via a display. What distinguishes this study from literature is its approach to determining the optimal coil geometry by correlating the current variation characteristics with the coil’s self-inductance coefficient and using Genetic Algorithm-based optimisation to identify the ideal projectile size that achieves maximum velocity under maximum force. Experiments with the developed coil gun showed that the projectile velocity change from the beginning of the first coil to the end of the fourth coil was linear.